Evaluation of Stature Development During Childhood and Adolescence in Individuals with Familial Hypophosphatemic Rickets - Mauro M.S. Borghi; Veronica Coates; Hatim A. Omar (The Scientific World Journal)
This review was conducted to study the diagnosis, treatment, and growth progression in infants and adolescents with familial hypophosphatemic rickets. The bibliographic search was carried out utilizing the electronic databases MEDLINE, OVID, and LILACS and by direct research within the last 15 years using the keywords rickets, familial hypophosphatemia, vitamin D deficiency, stature growth, childhood, and adolescence. Article selection was done by comparing the evaluation of the growth in patients with familial hypophosphatemic rickets, including the variables that might affect them, for possible future therapeutic proposals. It is concluded that the most significant fact in the treatment of familial hypophosphatemic rickets in infancy was the magnitude of the final stature. The use of growth hormone can be helpful in these patients. However, research reporting treatments with the use of the growth hormone for rickets are controversial. The majority of the authors agree that treatment using vitamin D and phosphate enables some statural growth in cases of early diagnosis, reflecting a better prognosis.